(1180) planning the volume of investment in the long-run period تخطيط حجم الاستثمار على المدى الطويل - srein, zdenek (the institute of national planning, 2018)
problems of finding the most suitable method for the determination of the volume of investment in the long-run period have not yet been sufficiently solved the theoretical studies and concept presented by a number of authors do not go beyond an econometric-model approach based on capital.